POLITICAL TIES AND FIRM PERFORMANCE IN CHINA: EVIDENCE FROM A QUANTILE REGRESSION. (22nd August 2017) - Xie, Wenjing; Liu, Keji; Xie, Fei; Ding, Haoyuan
Abstract: Whether political ties enhance or weaken firm performance has been widely investigated in a number of studies, including some on China. Based on a database of non-financial A-share listed firms from 2004 to 2012, we study the effects of political ties on firm performance within a quantile regression framework. We find that there is a positive relationship between political ties and economic performance, but that it is diminishing with respect to firm performance. Political ties appear particularly important for weaker firms.